2000
DOI: 10.1056/nejm200007273430404
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Staging of Non–Small-Cell Lung Cancer with Positron-Emission Tomography

Abstract: PET improves the rate of detection of local and distant metastases in patients with non-small-cell lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
419
0
36

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,010 publications
(473 citation statements)
references
References 16 publications
18
419
0
36
Order By: Relevance
“…The high NPV of 18 F-FDG PET/CT (up to 97%) for mediastinal disease6971 has led to the recommendation to omit mediastinoscopy in patients with negative mediastinal 18 F-FDG PET/CT 707273. However, special attention should be paid to central tumors, which have a high incidence of occult N2 disease 74.…”
Section: Methodsmentioning
confidence: 99%
“…The high NPV of 18 F-FDG PET/CT (up to 97%) for mediastinal disease6971 has led to the recommendation to omit mediastinoscopy in patients with negative mediastinal 18 F-FDG PET/CT 707273. However, special attention should be paid to central tumors, which have a high incidence of occult N2 disease 74.…”
Section: Methodsmentioning
confidence: 99%
“…For example, PET has been shown to have greater sensitivity and specificity than either CT or magnetic resonance imaging in the staging of lung cancer. ( 3 5 ) The delineation of lung‐tumor boundaries in CT images can be complicated by the presence of atelectasis, pleural effusion, pneumonitis, and displacement of normal tissue. Lymph node involvement, which is always of concern, is difficult to distinguish using CT scans alone.…”
Section: Introductionmentioning
confidence: 99%
“…Prevention of unnecessary surgical interventions has been reported to occur in up to 14% of patients [9]. Recently, a randomized study has shown that the number of futile thoracotomies was significantly reduced in 19/82 patients compared to 29/96 patients, based on the addition of fluorodeoxyglucose (FDG) PET to the diagnostic algorithm [8].…”
mentioning
confidence: 99%